Medieval horizons why the Middle Ages matter - Mortimer, Ian 1967- (The Bodley Head, 2023)
"We tend to think of the Middle Ages as a dark, backward and unchanging time characterised by violence, ignorance and superstition. By contrast we believe progress arose from science and technological innovation, and that inventions of recent centuries created the modern world. We couldn't be more wrong. As Ian Mortimer shows in this fascinating book, people's horizons - their knowledge, experience and understanding of the world - expanded dramatically. Life was utterly transformed between 1000 and 1600, marking the transition from a warrior-led society to that of Shakespeare. Just as The Time Traveller's Guide to Medieval England revealed what it was like to live in the fourteenth century, Medieval Horizons provides the perfect primer to the era as a whole. It outlines the enormous cultural changes that took place - from literacy to living standards, inequality and even the developing sense of self - thereby correcting misconceptions and presenting the period as a revolutionary age of fundamental importance in the development of the Western world."--
Keywords: Geschichte 1000-1600; Mittelalter; Kulturelle Entwicklung; Kulturwandel; Wissenschaftlicher Fortschritt; Europa; Middle Ages; Civilization, Medieval; Great Britain / Civilization / 1066-1485; Great Britain / Civilization / 16th century; Great Britain / History / Medieval period, 1066-1485; Great Britain / History / Tudors, 1485-1603; Civilization; Great Britain; 1066-1603; History